2015
DOI: 10.1136/annrheumdis-2015-eular.1653
|View full text |Cite
|
Sign up to set email alerts
|

AB0231 Factors Contributing to Delay in Use of Dmard Therapy in Early Rheumatoid Arthritis Patients

Abstract: BackgroundDelay of disease modifying anti-rheumatic drugs (DMARDs) therapy is an important factor for poor outcome in rheumatoid arthritis (RA).ObjectivesTo study the lag time between the onset of arthritis symptoms and the beginning of DMARD's therapy, and to determine factors associated with therapy delay.MethodsWe studied 70 consecutive patients with new RA onset (70% female, median age 60±14 years) admitted to the Department of Internal Medicine and Rheumatology, Military Institute of Medicine in Warsaw. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This study confirms the experience of other EAC worldwide – that patient delay predominantly contributes to overall delay, although this is not universal . We found that lower DAS28 and fatigue scores at baseline predicted a greater patient delay, possibly reflecting a more insidious onset of disease.…”
Section: Discussionsupporting
confidence: 87%
“…This study confirms the experience of other EAC worldwide – that patient delay predominantly contributes to overall delay, although this is not universal . We found that lower DAS28 and fatigue scores at baseline predicted a greater patient delay, possibly reflecting a more insidious onset of disease.…”
Section: Discussionsupporting
confidence: 87%